2021
DOI: 10.1136/bmjopen-2021-053095
|View full text |Cite
|
Sign up to set email alerts
|

Cancer symptom experience and help-seeking behaviour during the COVID-19 pandemic in the UK: a cross-sectional population survey

Abstract: ObjectivesTo understand self-reported potential cancer symptom help-seeking behaviours and attitudes during the first 6 months (March–August 2020) of the UK COVID-19 pandemic.DesignUK population-based survey conducted during August and September 2020. Correlates of help-seeking behaviour were modelled using logistic regression in participants reporting potential cancer symptoms during the previous 6 months. Qualitative telephone interviews with a purposeful subsample of participants, analysed thematically.Sett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
64
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(67 citation statements)
references
References 31 publications
(38 reference statements)
3
64
0
Order By: Relevance
“…Participants believed that the advent of the COVID-19 pandemic has exacerbated delays in help-seeking and subsequent LC diagnosis due to fear of contracting COVID-19 in healthcare facilities, stigma surrounding a cough during the pandemic, and prioritisation of COVID-19-related health concerns. This was demonstrated by a survey in the UK which found that approximately half of patients who reported experiencing cancer alarm signs and symptoms did not contact their GP due to concerns about catching or transmitting COVID-19, wasting the GP’s time, or putting an additional strain on healthcare services [ 11 ]. While some GPs perceived telephone consultations as helpful during the COVID-19 pandemic, other healthcare professionals felt the lack of in-person contact could lead to missed LC diagnosis, particularly when physical changes such as unplanned weight loss cannot be readily appraised during telephone consultations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Participants believed that the advent of the COVID-19 pandemic has exacerbated delays in help-seeking and subsequent LC diagnosis due to fear of contracting COVID-19 in healthcare facilities, stigma surrounding a cough during the pandemic, and prioritisation of COVID-19-related health concerns. This was demonstrated by a survey in the UK which found that approximately half of patients who reported experiencing cancer alarm signs and symptoms did not contact their GP due to concerns about catching or transmitting COVID-19, wasting the GP’s time, or putting an additional strain on healthcare services [ 11 ]. While some GPs perceived telephone consultations as helpful during the COVID-19 pandemic, other healthcare professionals felt the lack of in-person contact could lead to missed LC diagnosis, particularly when physical changes such as unplanned weight loss cannot be readily appraised during telephone consultations.…”
Section: Discussionmentioning
confidence: 99%
“…This delay, coupled with the impact of social and economic inequalities often associated with increased risk of LC [ 10 ], has detrimental effects on timely diagnosis, quality of life, cost of healthcare, and patients’ eligibility for curative treatment [ 6 ]. In recent years, COVID-19 has also had a detrimental impact on cancer help-seeking and diagnosis [ 11 ]. A survey of 7543 adults in the UK found that approximately half of patients who reported experiencing cancer alarm signs and symptoms did not contact their general practitioner (GP) due to concerns about catching or transmitting COVID-19 [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, patients and healthcare professionals are presented with the choice between remote appointments for non-urgent matters or the risk of infection in a face-to-face setting. While to a certain extend there is some evidence that remote consultations have been accepted well by the patients,41 several challenges have been reported too, especially in the case of people who suffer from pre-existing chronic conditions or who they may not feel comfortable with the use of technology 41–43. For those patients, implementation of immunity certificates for face-to-face appointments would be important in improving their sense of safety.…”
Section: Discussionmentioning
confidence: 99%
“…Urologists are also noticing a delay in consultation in some instances 144 , which could lead to increased morbidity and mortality, particularly in the field of oncology, in which the effect of missed diagnoses and delayed treatments might be devastating 145 . In the UK, 45% of patients with potential cancer symptoms (such as coughing up blood) did not contact their doctor in the first wave of the pandemic 146 . In urology, a dramatic decline in routine prostate cancer screening was observed 147 150 .…”
Section: Outlook For Covid-19 Pandemicmentioning
confidence: 99%